Laboratory investigations of Hb Constant Spring - Tangvarasittichai O. (2014)
Hb Constant Spring (HbCS), a nondeletional α-thalassemia, is most prevalent in southern Chinese and southeast Asian populations. In conjunction with α-thalassemia-1 or in the homozygous state, it is an important cause of HbH disease. The present study was designed to test the efficiency of different diagnostic methods in detecting HbCS. The following laboratory tests were applied to blood samples from 1000 pregnant women attending an antenatal clinic at Buddhachinaraj Hospital in Phitsanulok, Thailand: mutation specific restriction enzyme digestion (RED), amplification refractory mutation system (ARMS) and automated high-performance liquid chromatography (HPLC). The results demonstrate that the DNA-based methods, RED and ARMS, are efficient diagnostic tools in detecting HbCS in homozygotes and heterozygotes, whereas automated HPLC gave accurate results for homozygous HbCS, but misidentified (no peak) some cases of HbCS trait. Standard hematological methods (determination of mean cell hemoglobin and mean cell volume) did not efficiently differentiate homozygous HbCS and HbCS trait from samples with normal α-globin chains. We conclude that RED is the preferable method for HbCS screening and then confirmed diagnostic testing using ARMS. Cases unresolved by ARMS should be clarified by appropriate methods such as DNA sequencing. © 2005 Blackwell Publishing Ltd.